Autobiography of Mark Twain. Volume 2 [compact disc, unabridged] - Twain, Mark, 1835-1910 (Blackstone Audio, Inc., 2013)
Mark Twain's complete, uncensored autobiography was an instant bestseller when the first volume was published in 2010, on the centennial of his death. The second volume delves deeper into Twain's life, uncovering the many roles he played in his private and public worlds. Filled with his characteristic blend of humor and ire, the narrative ranges effortlessly across the contemporary scene. He shares his views on writing and speaking, and his contempt for the politics and politicians of his day.